Building a Sustainable Brand Relationship: Analysis of Brand Functional Value and Customer Emotional Cognition in Using the MyParmad Application - Aris Subagio; Dewi Kurniaty; Robby Isnaeni (Jurnal Manajemen dan Bisnis Madani, 2023)
This study examines the impact of brand functional value and customer emotional cognition on sustainable brand relationships between users and the MyParmad application. The results suggest that functional value has a more significant influence on the sustainable brand relationship than the emotional cognition of the customer. Nevertheless, emotional cognition is still an essential factor in promoting sustainable brand relationships based on the functional value of an application. By considering user feedback and implementing innovative ideas, organizations like Universitas Paramadina can improve their applications' functional aspects and strengthen their service concepts. Brand functional value and emotional cognition affect the formation of these relationships, and organizations like Universitas Paramadina can strengthen their service concepts by considering user feedback and implementing innovative ideas. The study used a purposive sampling technique to gather data from 103 Universitas Paramadina students via an electronic questionnaire during February-March 2023. The survey consisted of 28 Likert scale questions based on previous research on brand functional value, customer emotional cognition, and sustainable brand relationships.